Desenvolvimento de crianças com Trissomia 21: relação com o suporte social e a satisfação parental - Montes, Kananda Fernanda (2024)
Biological and external factors influence child development. Trisomy 21 is the most common biological alteration in humans, characterized as a genetically determined condition. Its particular characteristics can compromise the child's development, which in turn can cause changes in family dynamics. With this in mind, this study aimed to: (a) describe and relate social support and family parental satisfaction with the development of children with Trisomy 21 and (b) describe and relate sociodemographic data with child development, social support and family parental satisfaction of families of children with Trisomy 21. The participants in this study were 20 people responsible for children with Trisomy 21, aged between one and five years and 11 months. The evaluation measures were: Brazil Criteria Questionnaire, Social Support Questionnaire, Parental Satisfaction Scale, Operationalized Portage Inventory (OPI) and semi-structured interviews. The data was collected remotely, with the interview being the only instrument carried out asynchronously; the others were carried out in synchronous meetings. The qualitative data was obtained from the interview and the other instruments provided quantitative data which was analyzed using descriptive methods with the use of measures of central tendency and dispersion. Pearson's correlation test was used to correlate the variables. The main results were that none of the participants reported dissatisfaction with their parental role and, as a result, the level of parental satisfaction was high. The spouse was the most frequently mentioned support person and the items with the highest satisfaction averages were related to the perspective of the support people on the participants. The IPO data showed that the area of socialization was the one with the highest number of affirmative responses, while language was the area with the lowest performance by children with T21. Regarding correlations, parental satisfaction showed a positive correlation with all the areas of the IPO, and social support showed that the greater the number of supportive people, the better the development shown by the child with T21 in the areas of socialization and language. The age of the child revealed that the older the child, the lower the development in the areas of socialization, cognition, self-care and motor development. Physiotherapy, occupational therapy and speech therapy were the services that children with T21 received the most and psychological support was the service most requested by parents. The data from this study helps families to understand the impact that family variables have on the development of children with T21, as well as supporting early intervention programs with data on performance in each of the areas of child development.